2016
DOI: 10.1038/srep37157
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sirt1/Nrf2/TNF-α signaling pathway by luteolin is critical to attenuate acute mercuric chloride exposure induced hepatotoxicity

Abstract: Inorganic mercury, though a key component of pediatric vaccines, is an environmental toxicant threatening human health via accumulating oxidative stress in part. Luteolin has been of great interest because of its antiinflammatory, anticarcinogenic and antioxidative effects. Here we hypothesized that luteolin would attenuate hepatotoxicity induced by acute inorganic mercury exposure. Kunming mice were treated with luteolin (100 mg/kg) 24 h after administration of 4 mg/kg mercuric chloride (HgCl2). The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 53 publications
3
82
0
Order By: Relevance
“…The remarkable effects of luteolin in the alleviation of inflammation, allergies, cancers, anxiety, heart diseases, and oxidative insults have been previously reported [17][18][19][20][21]. Luteolin exerts defensive effects against liver injury caused by acetaminophen, mercuric chloride, and tetrachloromethane by restoring antioxidant power and mitigating the inflammatory mediators [22][23][24]. Furthermore, LUT has shown significant anti-peroxidative effects against CCl 4 -induced hepatotoxicity in rats [25].…”
Section: Introductionmentioning
confidence: 91%
“…The remarkable effects of luteolin in the alleviation of inflammation, allergies, cancers, anxiety, heart diseases, and oxidative insults have been previously reported [17][18][19][20][21]. Luteolin exerts defensive effects against liver injury caused by acetaminophen, mercuric chloride, and tetrachloromethane by restoring antioxidant power and mitigating the inflammatory mediators [22][23][24]. Furthermore, LUT has shown significant anti-peroxidative effects against CCl 4 -induced hepatotoxicity in rats [25].…”
Section: Introductionmentioning
confidence: 91%
“…Gadacha et al have reported that resveratrol acts as an antioxidant during the active phase and as a pro-oxidant during the inactive phase of rats [46], suggesting certain polyphenols have different effects depending on the intake timing. Several reports have revealed that high concentration of luteolin (80-100 mg/ kg) attenuates the liver injury and hepatotoxicity through the activation of Nrf2 [21,22]. Taken together, these results suggest that luteolin intake at the start of active phase may possess the powerful effect for prevention and amelioration to several diseases occurring from oxidative stress through the activation of Nrf2 even if the amount of luteolin is very low.…”
Section: Plos Onementioning
confidence: 67%
“…The serum concentration of luteolin reaches about 100 nM by dietary habit [19]. Luteolin possesses a lot of physiological functions including antioxidative activity [21,22], while the number of cultured cells and animal studies evaluate the effects in the concentration that exceeds the amount taken from the daily meal. On the other hand, our previous study revealed that the physiological nanomolarconcentration range of luteolin induces Nrf2/ARE pathway in human hepatoma HepG2 cells [23].…”
mentioning
confidence: 99%
“…) as in mammalian cells (Li et al ., ). In mammals, the phytochemicals luteolin (Yang et al ., ), curcumin (Poojan et al ., ), sulphoraphane (Philbrook & Winn, ), I3C, phenethyl isothiocyanate, protocatechuic acid and tannic acid (Krajka‐Kuźniak et al ., ) induced Nrf2 expression. In insects, the Nrf2 orthologue cap ‘n’ collar isoform‐C in Drosophila was induced by the xenobiotics phenobarbital, chlorpromazine and caffeine (Misra et al ., ).…”
Section: Discussionmentioning
confidence: 99%